Computed Tomography Analysis of the Ethmoid Roof: A Region at Risk in Endoscopic Sinus Injury - Urusopone, Pra (The ASEAN Journal of Radiology, 2019)
Objective: To determine the olfactory fossa depth according to the Keros classification and determine the incidence of asymmetry in height and configuration of the ethmoid roof. Materials and Methods: Retrospective analysis of 75 coronal computed tomography studies of paranasal sinuses and facial bones were performed. Measurement of the depth of the lateral lamella, classification of the depth according to Keros type and determination of the asymmetries in the ethmoid roof depth and configuration were done. Results: The mean height of the lateral lamella cribiform plate (LLCP) was 2.15+1.29 mm. The cases were classified as 87.33% Keros type1 and 12.67 % as Keros type 2. No Keros type 3 was found .There was asymmetry in the LLCP height of 33.33% of cases and a configuration asymmetry in 8% of the cases. No significant difference between the mean height and distribution of Keros type between gender and laterality were also found. Conclusion: As regards the olfactory fossa depth, the Keros type 1 was most frequently found. Asymmetry in the depth and configuration were detected in 33.33 and 8% respectively. Risk of inadvertent intracranial entry through the lateral lamella among Thai may be lower than other studies with majority of cases classified as Keros type 2 or 3.